Manifest disadvantages in undue influence: an analysis of its role and necessity - Callaghan, Catherine (Victoria University of Wellington Law Review, 1995)
In this article, the author examines the recent case law on the requirement of manifest disadvantage in the doctrine of undue influence and argues that the courts have misunderstood the role and relevance of this requirement. By determining what purpose or principle underlies the equitable jurisdiction, the author aims to show that proof of manifest disadvantage should not in fact be necessary in cases of either actual or presumed undue influence.